2014
DOI: 10.1104/pp.114.253898
|View full text |Cite
|
Sign up to set email alerts
|

Pepper Heat Shock Protein 70a Interacts with the Type III Effector AvrBsT and Triggers Plant Cell Death and Immunity  

Abstract: Heat shock proteins (HSPs) function as molecular chaperones and are essential for the maintenance and/or restoration of protein homeostasis. The genus Xanthomonas type III effector protein AvrBsT induces hypersensitive cell death in pepper (Capsicum annuum). Here, we report the identification of the pepper CaHSP70a as an AvrBsT-interacting protein. Bimolecular fluorescence complementation and coimmunoprecipitation assays confirm the specific interaction between CaHSP70a and AvrBsT in planta. The CaHSP70a pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 64 publications
0
50
0
Order By: Relevance
“…It was demonstrated that transient overexpression of a cytoplasmic pepper (Capsicum annuum) HSP70 (HSP70a) during heat stress or Xanthamonas campestris pv vesicatoria infection caused cell death in pepper leaves (Kim and Hwang, 2015). Chen et al (2008) did not observe increased expression for any of the six HSP70 gene family members after infecting N. benthamiana plants with a PVX VIGS vector harboring a fragment of NbHSP70c-1.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that transient overexpression of a cytoplasmic pepper (Capsicum annuum) HSP70 (HSP70a) during heat stress or Xanthamonas campestris pv vesicatoria infection caused cell death in pepper leaves (Kim and Hwang, 2015). Chen et al (2008) did not observe increased expression for any of the six HSP70 gene family members after infecting N. benthamiana plants with a PVX VIGS vector harboring a fragment of NbHSP70c-1.…”
Section: Discussionmentioning
confidence: 99%
“…HSP70 is involved in protein translocation, folding, synthesis, and macromolecular assemblies (Hartl and HayerHartl 2002;Mayer and Bukau 2005). Pepper heat shock protein 70a (CaHSP70a) physically interacts with AvrBsT in yeast and in planta (Kim and Hwang 2015b). Agrobacterium-mediated transient expression assays and Co-IP assays in N. benthamiana showed that AvrBsT directly binds to CaHSP70a in planta (Kim and Hwang 2015b).…”
Section: Pepper Aldehyde Dehydrogenase1 (Caaldh1)mentioning
confidence: 98%
“…Pepper heat shock protein 70a (CaHSP70a) physically interacts with AvrBsT in yeast and in planta (Kim and Hwang 2015b). Agrobacterium-mediated transient expression assays and Co-IP assays in N. benthamiana showed that AvrBsT directly binds to CaHSP70a in planta (Kim and Hwang 2015b).…”
Section: Pepper Aldehyde Dehydrogenase1 (Caaldh1)mentioning
confidence: 99%
See 1 more Smart Citation
“…These proteins protect cells against harmful effects of stress conditions. Heat shock proteins (HSPs), also known as molecular chaperones, are known to belong among these stress proteins while they are present in all living organisms (Kim & Hwang 2015). Besides their role in protecting cells against environmental stress conditions, HSPs are essential components of plant cells and they play an important role in protein stabilisation and cellular functions related with plant growth (Pratt et al 2001;Koo et al 2015).…”
mentioning
confidence: 99%